Supervisory oral and written feedback on postgraduate EFL students' thesis drafts - Abdulkhaleq, Mohammed Mohammed (2014)
The provision of supervisor feedback on the draft of postgraduate students’ thesis is an important academic practice that helps students make progress with their writing and research skills. Researchers interested in EFL writing have sought to understand the nature and quality of supervisor feedback; however, pragmatic and/or rhetorical influences of supervisor feedback on students’ writing development, are still under research. The present study investigated the various types of written and oral feedback provided by supervisors at the postgraduate level, the distribution of the feedback across the various pragmatic and rhetorical functions in thesis drafts relative to the earlier stages of the student’s development as a researcher, student perceptions about supervisor feedback, and the extent to which feedback was used to revise drafts. The study benefited from a broad theoretical framework that covered research on supervision models, situated learning and community of practice, speech functions model, and rhetorical strategies. A qualitative case study approach was adopted in this study to explain and understand the meanings and process of the supervisory oral and written feedback in their natural setting in an EFL setting. This design provided a chance for a clear manifestation of how students work in the postgraduate context. That leads to an in-depth investigation of the feedback process and activities. Purposive sampling was used in this study to discover, understand, and gain insight about feedback practices as situated in the academic community of practice. The data for this study was procured from different sources; supervisors’ written feedback on students’ theses, audio taping oral feedback conferences, conducting interviews with students, and collecting evaluation sheets completed by supervisors on their students’ incorporation of feedback. Data were qualitatively analyzed in tandem with how and to what extent students revised their thesis drafts after feedback. In the case of the supervisors who participated in the study, it was found that they used rhetorical devices such as logic, euphemism, rhetorical question, and speech functions such as criticism, praise, and information regarding content. They appeared to focus their feedback mainly on matters related to thesis structure, writing style,flow of ideas, and organization of the thesis. These main categories provided the bases for other sub-themes that emerged from the data. Together these were then used to form a new model that can be used by supervisors to provide effective draft feedback. As might be expected, the students involved in the study generally perceived their supervisor feedback as useful and helpful. However, students’perceptions of, and their incorporation of, supervisors’ feedback were convoluted and entangled with not only supervisors’ feedback practices and methods, but also other factors such as a student’s cultural background, language proficiency level, and research experience. It was apparent that the participants generally appreciated the supervisors’ feedback and showed a keen interest in applying the feedback given to them on their drafts. However, the students did not appreciate the feedback given on grammar and punctuation, or feedback that carried ambiguity. It was also found that oral feedback conferencing was of value to good students but not to struggling students. It was concluded that supervisor-supervisee rapport plays a crucial role in improving the overall quality of supervision. Improving rapport helped establish a good dialogical environment that led to better relationships and hence better outcomes. In summary, the present study provided insights useful to postgraduate EFL students as well as their supervisors on how to make feedback more effective in postgraduate supervision. The findings are also deemed to have implications for the development of written and oral feedback models in postgraduate supervision.